E-tourism atlas: a web-multimedia tourism mapping system and mobile apps in Malaysia / Muhammad Nurrahim Ruslan ... [et al.] - Ruslan, Muhammad Nurrahim; Abdul Rasam, Abdul Rauf; Mohamed Saraf, Noraain; Salleh, Siti Aekbal (Universiti Teknologi MARA, Kedah, 2019)
Tourism is one of the main sectors that have hugely contributed in Selangor’s economy by generating incomes from local tourist and foreign tourists who come to Selangor for vacations. The rapid growth of digital technology that have been affecting tourism sector by make it easier for tourist to gain information about the tourist attraction places through their computer or smartphone. An innovation of e-tourism atlas is developed to implement the cartographic knowledge and GIS techniques in Selangor Tourism, Malaysia. By using this GIS and web-multimedia tourism information system, the users can increase integrity and accuracy of the data especially the locations of the attraction places in the state. This proposed system can support usage on Windows operating system for computer or laptops platform and Android operating system that compatible for smartphone. The system has also navigation functions that will assist users to navigate their ways to intended locations. Besides that, it provides useful tourism information such as general information of the place, operational hour, entrance fee and gallery of pictures. Multimedia elements are also included in the system such as audio, graphics, animation and video in order to attract the attentions of users or tourists. Overall, the selected respondents have agreed and satisfied with the functions developed in the system to easily access and disseminate the related tourism information.